2018
DOI: 10.1002/jctb.5802
|View full text |Cite|
|
Sign up to set email alerts
|

Which activated sludge configurations qualify for maximizing energy conservation – Why?

Abstract: BACKGROUND This paper aimed to provide a critical appraisal on maximizing sludge generation and energy conservation in high‐rate activated sludge (AS) configurations. The role of gravity settling and the positive attributes of high rate membrane bioreactors were emphasized. The appraisal covered data reported in the literature on 40 different experiments testing high‐rate AS configurations for sludge generation and energy conservation. RESULTS In systems with gravity settling, effluent chemical oxygen demand (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…It is interesting to note that 24% to 48% of COD (i.e., an average of 60% of COD removed) was converted into sludge; however, 19% to 50% of the sludge — an average of 35% — escaped the settler into the next B stage, which basically operated as an activated sludge process with an inflow of particulate substrate and active biomass 22 . Thus, the observed sludge/energy recovery in the A stage was reduced to 44%, which is lower than what can be achieved in most conventional activated sludge configurations 5,23 . The results summarized in Table 3 provide a clear indication that the main bottleneck of the A process is sustaining the presumed high biomass/COD recovery, mainly due to the fragile nature of the flocs.…”
Section: The a Processmentioning
confidence: 89%
See 1 more Smart Citation
“…It is interesting to note that 24% to 48% of COD (i.e., an average of 60% of COD removed) was converted into sludge; however, 19% to 50% of the sludge — an average of 35% — escaped the settler into the next B stage, which basically operated as an activated sludge process with an inflow of particulate substrate and active biomass 22 . Thus, the observed sludge/energy recovery in the A stage was reduced to 44%, which is lower than what can be achieved in most conventional activated sludge configurations 5,23 . The results summarized in Table 3 provide a clear indication that the main bottleneck of the A process is sustaining the presumed high biomass/COD recovery, mainly due to the fragile nature of the flocs.…”
Section: The a Processmentioning
confidence: 89%
“…The last set of experiments (C2) was all fed by chemically enhanced primary effluent and involved different HRAS configurations also including contact stabilization, operated at a θ X range of 0.2–0.7 days 27 . A comprehensive critical appraisal of these studies was made, accounting all key parameters (such as the sludge age, the observed yield, hydraulic retention time, and reactor configuration) likely to affect reported results 23 . The magnitude of effluent COD and its partition between soluble and particulate fractions derived in this appraisal is displayed in Fig.…”
Section: Scientific Studiesmentioning
confidence: 99%
“…Table summarizes the energy conservation potential of six commonly used AS configurations operated without primary settling, in the wide SRT range of 0.5 to 50.0 days, based on an influent COD level of 500 mg L −1 , corresponding to an energy level of 1625 kcal m −3 ; the evaluation displayed in Table , clearly shows the merit of low SRT operation, where the rate of energy conservation increases from 23% in slow rate membrane reactor (SRT 50 days) to above 55–60% in SFMBR (SRT < 2.0 days). Similar studies also provided convincing scientific evidence that the practice of energy conservation should not be attempted with some AS configurations such as the contact stabilization process, since the corresponding flow scheme is not suitable for energy conservation . Targeting enhanced excess sludge generation in high rate AS systems for energy recovery would inevitable increase the cost of sludge dewatering.…”
Section: Reshaping the Processmentioning
confidence: 90%
“…Furthermore, activated systems with gravity settling also suffer from biomass escape from the settler, incorporating an additional particulate COD load into the effluent. In a review on the performances of such systems, it was reported that the effluent particulate COD fluctuated between 100-200 mg/L when the SRT selected for operation was below 1.0 d [60].…”
Section: Effluent Qualitymentioning
confidence: 99%